2016
DOI: 10.1002/hipo.22661
|View full text |Cite
|
Sign up to set email alerts
|

MRI uncovers disrupted hippocampal microstructure that underlies memory impairments after early‐life adversity

Abstract: Memory and related cognitive functions are progressively impaired in a subgroup of individuals experiencing childhood adversity and stress. However, it is not possible to identify vulnerable individuals early, a crucial step for intervention. In this study, high-resolution magnetic resonance imaging (MRI) and intra-hippocampal diffusion tensor imaging (DTI) were employed to examine for structural signatures of cognitive adolescent vulnerabilities in a rodent model of early-life adversity. These methods were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 102 publications
(133 citation statements)
references
References 68 publications
(107 reference statements)
10
122
1
Order By: Relevance
“…A recent study revealed a widespread and pronounced loss of dendritic spines in MS cortex independent of cortical demyelination and axon loss 2. The latest evidence using combined MRI and histopathology suggests that, in principle, the DTI‐based measures of the cortex can reflect dendrite pathology,46, 47 which is a possible explanation for the widespread changes of DTI‐based measures in the cortex of MS patients 30, 39, 40, 41…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed a widespread and pronounced loss of dendritic spines in MS cortex independent of cortical demyelination and axon loss 2. The latest evidence using combined MRI and histopathology suggests that, in principle, the DTI‐based measures of the cortex can reflect dendrite pathology,46, 47 which is a possible explanation for the widespread changes of DTI‐based measures in the cortex of MS patients 30, 39, 40, 41…”
Section: Discussionmentioning
confidence: 99%
“…Third, the type and difficulty of the test that is used to measure behavioral outcomes is important. For example, a rigorous test such as object location memory (OL) might uncover subtle deficits not apparent in a less challenging test, such as object recognition memory (OR) [69]. These caveats are illustrated below.…”
Section: Modeling the Behavioral Outcomes Of Early-life Stressmentioning
confidence: 99%
“…For example, in a rigorous and hippocampus-dependent test of OL memory, an overt impairment in spatial memory was found as early as adolescence in LBN rats [69]. A less rigorous memory task for OR found comparable performance in LBN vs. Control adolescent rats.…”
Section: A Spectrum Of Cognitive Consequences Of Chronic Early-life Smentioning
confidence: 99%
See 2 more Smart Citations